Philosophy of “Soft Law” as a Universal Regulator of International Relations Management - Ortynskyi, Volodymyr; Shamrayeva, Valentina; Zeman, Ihor; Lisna, Ivanna; Valetska, Oksana (Տիգրան Մեծ)
Soft law is a set of rules and guidelines, the legal force of which is at the “negotiation” stage. It has ap-peared in international law since the 1970sas one alternative to international treaties, used in cases where, for various reasons, the parties do not want or cannot commonly decide or to sign an international treaty. Agreements of this kind do not create legal obligations between the contracting parties (under the principle, contracts must be respected) but only set political obligations, observing which is at the discretion of the parties. The primary purpose of the study is to analyze the philosophy of “soft law” in the context of international management of relations. The principal object of the research is the essence and significance of the philosophy of “soft law” as such. The major results of our research are to determine the essence and significance of the philosophy of “soft law” in the context of international relations.
Keywords: Philosophy